Kepatuhan pesakit HIV positif terhadap rawatan Highly Active Antiretroviral Therapy (HAART) - Najwa Afiqa Roshaizad,; Haikal Anuar Adnan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
HIV positive outbreak cases in Malaysia and the world are increasing from day to day. Many factors were associated with HIV positive especially homosexual activities. However, the issue of treatment for people living with HIV still need to be discussed in details. This issue is important to be discussed because it is one of the effective prevention measure nowadays. However, there are still vast amount of HIV patients have no knowledge about the treatment and the adherence level is low. The focus of this study is to examine adherence towards HAART treatment among HIV positive patients. This study used full qualitative method to collect and analyze data. Eight informants from Rumah Teduhan Kasih Sungai Buloh were interviewed separately using semi structured interview method. Among the topics discussed in this study were motivation to pursue treatment, adherence to medicine and appointments, reminder to take medicine and desire to stop treatment. The findings showed that, informans’ perception towards HAART is positive, highly motivated, adhere to appointment and medicine firmly and do not have intention to stop HAART treatment. For conclusion, adherence level for all informants were great. Nevertheless, treatment for people living with HIV issue still need to be discussed and promoted to ensure their well-being.